The Regeneration Crisis and Degradation of Traditional Garut Dodol Packaging: A Threat to Sundanese Culinary Cultural Identity - Sema Wulandari; Rani Windi Ayu S; Sakila Nanda Sifa; Tia Devani Vanessa; Itto Turyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Dodol Garut is a traditional culinary product of Garut Regency, West Java, which has held historical, economic, and cultural significance since 1926. Its natural-material packaging is a key element shaping the product's cultural identity. However, amid modernization and globalization, two interrelated phenomena have emerged: (1) a regeneration crisis among artisans threatening traditional knowledge continuity, and (2) a packaging degradation from natural to synthetic materials, eroding local wisdom values. This study employs a literature review method with a qualitative-descriptive approach and critical analysis of scholarly sources. The findings indicate that the packaging shift is not merely aesthetic, but reflects weakening intergenerational knowledge transmission and erosion of Sundanese visual cultural identity. Locally-based packaging innovation such as integration of Garutan batik motifs and MSME mentoring has proven to enhance competitiveness while preserving cultural identity. Comprehensive preservation strategies are needed, including local-wisdom-based education, UMKM designer collaboration, eco-friendly packaging evaluation, and government policies supporting traditional product authenticity.